DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS. - Alijonova Gulhayo; Jalolova M (TADQIQOTLAR, 2025)
In recent decades, early foreign language education has gained increasing global attention. Many educators and policymakers advocate for introducing foreign languages at the primary school level, arguing that younger learners have a natural ability to acquire new languages more effectively than adolescents or adults (Lightbown & Spada, 2013). Indeed, children possess greater neural plasticity and imitate sounds more accurately, which makes them ideal candidates for early language instruction (Lenneberg, 1967). However, despite these advantages, teaching foreign languages to young learners presents a number of complex challenges that are often overlooked.